Organic Matter Load in Pangean Reservoir Pangean District, Kuantan Singingi Regency, Riau Province - Darwinda Darwinda; Asmika Harnalin Simarmata; Tengku Dahril (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2020)
AbstractPangean reservoir is one of the reservoirs in Pangean district which has a primary function as a irrigation, PDAM and has been used for floating cage fish culture activities. Increasing fisheries activities will increase organic matter that enter the water and and as a consequence it affect water quality in general. A study aims to understand the organic matter load in Pangean Reservoir has been conducted in July-August 2019. Samples were taken from four station, once/week for a weeks. In each station there were 3 sampling point surface, 2 Secchi depth and 4 Secchi depth. Determination of daying coefficient was based on the BOD timeseries (2,4,6,8,10 day). Water quality parameter measured were temperature, transparency, depth, pH, dissolved oxygen, and BOD5. Result shown that decaying coefficient was 0,24-0,124 k/day, temperature was 29-31oC, transparency was 92-102 cm, depth was 248-388 cm, pH was 4-5, dissolved oxygen was 5-6,2 mg/L and BOD5 was 9,6-22,4 mg/L. The decaying coefficient and BOD intertime value indicate that the organic matter in the Pangean reservoir represent as load (P<B) in the water, as the decaying rate is slower than the input rate of organic matter. Keywords : BOD timeseries, decaying coefficient, dissolved oxygen, water quality